Application of simulink-control system toolbox for controlling and enzymatic reaction - 191408 Ng, Poh Leng (Sekudai : UTM, 1999)
Project Paper (Bachelor of Bioprocess Engineering) - Universiti Teknologi Malaysia, 1999